The ascent of money : [compact disc, unabridged] : a financial history of the world - Ferguson, Niall (Tantor Media, 2008)
Chronicles the evolution of finance from its origins in Mesopotamia to the modern world's most recent upheavals, covering such topics as the stock market bubble that prompted the French Revolution and the theories behind common investment vehicles.